The Space Agent - Ralph L. Reeder (Journal of Applied Communications, 1970)
Nothing has frightened me more through the years than the anticipatory commendation, as in my wife's "Will the rest of the house look as good as the side you painted last spring?" Or as in Dr. Brice Ratchford's July AAACE meeting comment, "Editors tend to be audience conscious."